The Influence of Tax Planning Vs Aggressive Tax Planning on Company Value in Domestic and Foreign Companies: Literature Review - Indri Nugraha; Ida Farida Adi Prawira (Universitas Muhammadiyah Makassar, 2024)
The purpose of this research is to analyze the impact of Tax Planning and Aggressive Tax Planning on company value. Tax Planning, measured using three indicators—Cash Effective Tax Rate, Book Tax Difference, and Tax Shelter—was found to have a significant influence on company value. Conversely, Aggressive Tax Planning showed no significant effect on company value. This study employs the Systematic Literature Review (SLR) method, utilizing a sample of 30 journal articles as the primary data source. The SLR approach enables a comprehensive analysis by synthesizing findings from multiple studies, ensuring robust and reliable conclusions. The findings highlight the importance of effective tax planning strategies in enhancing company value while suggesting that overly aggressive tax planning may not yield the desired benefits for firms. These results underscore the need for companies to adopt balanced and sustainable tax strategies to optimize their financial performance and long-term value. Future research is encouraged to explore additional factors influenced by Tax Planning and Aggressive Tax Planning. This may include examining their impact on other financial performance metrics, governance structures, or stakeholder trust. Furthermore, the study's implications can guide policymakers and practitioners in designing tax frameworks and strategies that align with corporate value creation objectives. Ultimately, this research serves as a valuable reference for academics, practitioners, and policymakers, providing insights into the nuanced effects of tax strategies on firm value and laying a foundation for future investigations.